RESEARCH ON THE IMPACT OF DIGITAL TRANSFORMATION ON THE QUALITY OF MANAGEMENT OF INDUSTRIAL ENTERPRISES ON THE BASIS OF SUSTAINABLE DEVELOPMENT - Станьковська, Ірина; Смага, Любомир (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The purpose of the work is to study the impact of digital transformation on the quality of management of industrial enterprises on the basis of sustainable development. The objectives of the study are: to study the impact of digital transformation on the practice of improving the quality of management at Ukrainian industrial enterprises with a focus on the role of digital tools; to study the impact of digital transformation on the sustainability of industrial enterprises; to identify obstacles to the implementation of digital technologies at Ukrainian enterprises, focusing on the challenges associated with access to technology, financing and qualified personnel; to assess the level of digital transformation and sustainability of industrial enterprises as the basis for ensuring the quality of enterprise management. The research used methods of analysis and synthesis, comparison, scientific generalization, and modeling. To solve the tasks set, the scientific works of domestic and foreign scientists were analyzed. The directions for improving the quality of enterprise management based on digital transformation were identified. Sustainability in the context of digital transformation was considered and the contribution of digital technologies to ensuring the sustainability of industrial enterprises was highlighted. The problems faced by Ukrainian enterprises when implementing digital technologies are analyzed, namely: lack of finance, limited access to technologies, lack of qualified personnel and cultural resistance. To improve the quality of enterprise management, the components of the proposed “Digital Transformation and Sustainability Assessment Model” (DTSAM) were used. This model provides a structured basis for assessing the current state of digitalization and efforts towards sustainable development of an industrial enterprise. To assess the quality of enterprise management based on the model, an evaluation algorithm and classification criteria were applied, taking into account the digital maturity of the enterprise and compliance with the principles of sustainable development.